Franz Rosenzweig and the crisis of german historicism - Navarrete, Roberto (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper deals with the genesis of the Third Part of Franz Rosenzweig’s Star of Redemption and his Judesein characterization from his metapolitical and metahistorical existence and as opposed to the Messianic Politics of the Peoples of the World. The starting point of the research will be the Rosenzweigian study of the origins and development of the Hegelian idea of State, Hegel und der Staat, as well as some relevant political writings which Rosenzweig wrote during the First World War. In spite of the traditional interpretation of Rosenzweig’s intellectual and vital course, we propose here to locate the roots of his judaization and his comprehension of Jewish Dasein specificity not only in his contacts with E. Rosenstock-Huessy and H. Cohen but also in his war experience and his deep disillusion about the connection between Politics and History which is at the very core of Hegelian philosophy and of F. Meinecke’s Ideengeschichte.